The Importance of English in The Development of The Tourism Sector in Banda Aceh - Marisa Yoestara; Zaiyana Putri; Isnaini Putri (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2021)
This study aims to find out how important the use of English is in developing the tourism sector in Banda Aceh and to find out how English is currently used in the development of the tourism sector in Banda Aceh. The research method used a mixed-method design. The research participants were the leaders and staff at the Banda Aceh City Tourism Office, Kana Tour and Travel, MU Wisata Tour and Travel Company, and Awa Tour and Travel which consists of 30 people, they are 4 leaders and 26 staff. This study used questionnaires and interviews as the instruments. The formula used to analyze the questionnaire data was the percentage formula from the Likert scale, and the interviews results were done through data transcription. After collecting data, it was found that based on the questionnaire answers of the staffs (at Banda Aceh City Tourism Office and Travel Agencies), the results of using English in the development of the tourism sector in Banda Aceh reached 93% which were considered important, and only 7% were not important. Meanwhile, currently in the tourism sector in Banda Aceh, English was also very important to use. These results are based on the interview answers of the leaders (at the Banda Aceh City Tourism Office and Travel Agencies). But the reasons for using it were different, such as making tour packages, providing tourism information, managing travel documents, interacting with international customers, carrying out activities in their respective fields, and working with other relevant agencies.